Ocean acidification: Linking science to management solutions using the Great Barrier Reef as a case study. (1st November 2016) - Albright, Rebecca; Anthony, Kenneth R.N.; Baird, Mark; Beeden, Roger; Byrne, Maria; Collier, Catherine; Dove, Sophie; Fabricius, Katharina; Hoegh-Guldberg, Ove; Kelly, Ryan P.; Lough, Janice; Mongin, Mathieu; et al.
Abstract: Coral reefs are one of the most vulnerable ecosystems to ocean acidification. While our understanding of the potential impacts of ocean acidification on coral reef ecosystems is growing, gaps remain that limit our ability to translate scientific knowledge into management action. To guide solution-based research, we review the current knowledge of ocean acidification impacts on coral reefs alongside management needs and priorities. We use the world's largest continuous reef system, Australia's Great Barrier Reef (GBR), as a case study. We integrate scientific knowledge gained from a variety of approaches (e.g., laboratory studies, field observations, and ecosystem modelling) and scales (e.g., cell, organism, ecosystem) that underpin a systems-level understanding of how ocean acidification is likely to impact the GBR and associated goods and services. We then discuss local and regional management options that may be effective to help mitigate the effects of ocean acidification on the GBR, with likely application to other coral reef systems. We develop a research framework for linking solution-based ocean acidification research to practical management options. The framework assists in identifying effective and cost-efficient options for supporting ecosystem resilience. The framework enables on-the-ground OA management to be the focus, while not losing sight of CO2 mitigation as the ultimate solution. Highlights: Ocean acidification knowledge is reviewed alongside management needs/priorities. A framework is developed to link acidification research to management options. The framework helps identify options to support coral reef ecosystem resilience.